A Randomized Control Trial Evaluating an Online Mindful Parenting Training for Mothers With Elevated Parental Stress - Potharst, Eva S.; Boekhorst, Myrthe G. B. M.; Cuijlits, Ivon; van Broekhoven, Kiki E. M.; Jacobs, Anne; Spek, Viola; Nyklíček, Ivan; Bögels, Susan M.; Pop, Victor J. M. (Frontiers in Psychology, 2019)
Objectives The prevalence of maternal stress in early years of parenting can negatively impact child development. Therefore, there is a need for an early intervention that is easily accessible and low in costs. The current study examined the effectiveness of an 8-session online mindful parenting training for mothers with elevated levels of parental stress. Methods A total of 76 mothers were randomized into an intervention (n = 43) or a waitlist control group (n = 33). The intervention group completed pretest assessment prior to the online intervention. Participants completed a post intervention assessment after the 10 weeks intervention and a follow-up assessment 10 weeks later. The waitlist group completed waitlist assessment, followed by a 10-week waitlist period. After these 10 weeks, a pretest assessment took place, after which the waitlist group participants also started the intervention, followed by the posttest assessment. Participating mothers completed questionnaires on parental stress (parent-child interaction problems, parenting problems, parental role restriction) and other maternal (over-reactive parenting discipline, self-compassion, symptoms of depression and anxiety) and child outcomes (aggressive behavior and emotional reactivity) while the non-participating parents (father or another mother) were asked to also report on child outcomes. Results The online mindful parenting intervention was shown to be significantly more effective at a 95% level than a waitlist period with regard to over-reactive parenting discipline and symptoms of depression and anxiety (small and medium effect sizes), and significantly more effective at a 90% level with regard to self-compassion, and mother-rated child aggressive behavior and child emotional reactivity (small effect sizes). The primary outcome, parental stress, was found to have a 95% significant within-group effect only for the subscale parental role restriction (delayed small effect size improvement at follow-up). No significant improvements on child outcomes were found for the non-participating parent. Conclusions To conclude, the results provide first evidence that an online mindful parenting training may be an easily accessible and valuable intervention for mothers with elevated levels of parental stress.